Women’s Matrimonial Role in Classical Chinese Literature: A Case Study of the Protagonist in Shen Fu’s Six Records of a Floating Life: Peran Perkawinan Perempuan dalam Sastra Tiongkok Klasik: Sebuah Studi Kasus tentang Tokoh Utama dalam Enam Catatan Kehidupan Mengambang karya Shen Fu - Wang, Aiqing (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Fusheng Liu Ji ‘Six Records of a Floating Life’ is the autobiographical prose composed by an intellectual Shen Fu in the High Qing era, which chronicles his impoverished life featured by both sorrow and exaltation. A substantial portion of the work concerns Shen’s wife named Yun, who is adulated as one of the most meritorious women in Chinese literature by an illustrious writer and translator Lin Yutang. From a pre-modern perspective, in her postnuptial life, Yun complies with the Confucian teachings prescribing women’s conduct, virtue and demeanour, viz. ‘Three Obediences and Four Virtues’; additionally, Yun exhibits filial piety which is also a preponderant creed in imperial China. From a modern perspective, Yun demonstrates proto-feminist thinking and sentimentality that defy orthodox institutions, embodied by her courageous cross-dressing and harmonious matrimonial relationship enriched by profound emotional devotion and physical intimacy. Furthermore, Yun is equipped with intelligence, generosity, romantic spirit and artistic temperament, and is hence eulogised by her husband for possessing a mentality and merits like a man, which, I posit, is the ultimate accolade in a patriarchal context.